White crow : the life and times of the Grand Duke Nicholas Mikhailovich Romanov : 1859-1919 - Cockfield, Jamie H. (Praeger, 2002)
Based on material from Russian archives, this is the biography of Nicholas Mikhailovich Romanov (1859-1919), the only intellectual in the Russian Imperial Family. This study provides insight into the last six decades of tsarist Russia through the experiences of the "oddball" member of the clan